A method for improving the accuracy of infrared thermometry under the influence of dust. Issue 21 (2018) - Pan, Dong; Jiang, Zhaohui; Gui, Weihua; Yang, Chunhua; Xie, Yongfang; Jiang, Ke
Abstract: The dust created in the industrial process is an important factor that has an influence on the accuracy of infrared thermometry, but it is often neglected. In order to reduce the influence of dust on infrared thermometry, a method for improving the accuracy of infrared thermometry under the influence of dust is proposed. In this study, based on the principle of infrared thermometry and dust transmittance, a compensation model is established to compensate the measurement result of infrared thermal imager under the influence of dust. Experimental results have demonstrated the effectiveness of the proposed model.